Effects of density on growth and survival of juvenile Red Swamp Crayfish, Procambarus clarkii (Girard), reared under laboratory conditions - Ramalho, Ricardo Oliveira (2012)
The aim of this study was to quantify the importance of population density on the growth and survival of juvenile red swamp crayfish, Procambarus clarkii (Girard), and to understand the effects of density on both the period between moults and the increment per moult at high densities without food limitation. A laboratory experiment was performed to determine growth and survival of juvenile crayfish at five densities (20, 40, 60, 80 and 100 crayfish m−2). Density clearly affected crayfish growth. The impact of density on final weight was higher than on total length increase, growth rate and final length (FL) (by decreasing order of effect). When comparing minimum and maximum densities, we observed that FL suffered a 34% reduction. Number of moults, mean intermoult period (IP) and survival were not significantly affected by density. Our results indicated that the IP and the percentage of increment per moult are affected by the size of crayfish before moult and we provide equations for these relations. Our findings are relevant both for crayfish aquaculture management and for the management of wild or harvested rice-field crayfish populations.